Facile synthesis of Fe3+/Fe2+ self-doped nanoporous FeVO4 photoanodes for efficient solar water splitting. Issue 6 (26th January 2017) - Wang, Wei; Zhang, Yajun; Wang, Lei; Bi, Yingpu
Abstract : We demonstrated a facile and effective method to fabricate nanoporous FeVO4 photoanodes for efficient solar water splitting. More importantly, the rationally self-doped Fe 2+ or Fe 3+ on the FeVO4 photoanode could further improve the photoelectrochemical (PEC) performance. Abstract : We demonstrated a facile and effective method to fabricate nanoporous FeVO4 photoanodes for efficient solar water splitting. More importantly, the rationally self-doped Fe 2+ or Fe 3+ on the FeVO4 photoanode could further improve the photoelectrochemical (PEC) performance, which may provide an alternative approach for the design and construction of low-cost and highly efficient PEC systems.